Marketing Mix Strategy (7P) for Islamic Boarding School-Based School Marketing - Astri Ibadiyah; Agus Hermawan; Imam Mukhlis (CV. AFDIFAL MAJU BERKAH, 2022)
This research is based on the fact that educational institutions are always interesting to study. Especially This research is based on the fact that educational institutions are always interesting to study. Especially related to marketing carried out by each institution. It should be noted that educational institutions are service institutions whose essence is that educational institutions can satisfy users of educational services. Every individual has wants and needs related to Education. If satisfied, it will affect the quality of the educational institution. When there is a demand, the customer wants services at the educational institution through programs, then the educational institution conveys the program, then there is a transaction or communication which results in customer satisfaction. The success of education is based on; 1) the magnitude of the interest of prospective students, 2) the increase in the quality of education services, 3) the emergence of satisfaction from education customers. These three things will be realized if supported by the right marketing strategy. So we need a marketing strategy that is in accordance with educational services, which is known as the 7P marketing mix which consists of three elements, namely people, process, and physical evidence. This research uses qualitative research with the type of case study with a multi-case design. Where the researchers conducted a theoretical and in-depth study at two research locus, namely the SMP Mambaus Sholihin Sanankulon Blitar and SMP Bustanul Muta’allimin Dawuhan Blitar. Based on the results of the study it was found that; 1) People in the marketing mix for the school's marketing strategy are the most basic, namely the selection of new student admissions, having superior graduate competencies, excelling in the field of the Qur'an as a guide for Muslims, and financial services that are accountable, friendly, and fast. 2) The process in the marketing mix for the school's marketing strategy is through the implementation of Islamic boarding school education, then promotion through websites, brochures, social media. Then the publication through spiritual teachers, and promotion through the sister school program. 3) Physical evidence in the marketing mix for the school's marketing strategy is to have a strategic school location, a clean and green environment, a magnificent building with complete facilities.